2019
DOI: 10.22354/in.v23i3.791
|View full text |Cite
|
Sign up to set email alerts
|

Detección del virus del papiloma humano en mucosa oral de mujeres de Cali, Colombia

Abstract: Introducción: Poco se sabe acerca de la presencia del VPH en la mucosa oral en población sana y cuales son los factores de riesgo que pueden llevar al virus a una infección persistente que conduzca al desarrollo de un carcinoma.Objetivos: en el presente estudio la detección del VPH se realizó en muestras de ADN obtenidas de la mucosa oral de 76 mujeres sanas.Métodos: el VPH se detectó mediante la técnica de PCR anidada para el gen viral L1. La genotipificación se realizó mediante la secuenciación directa del f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…2 Studies conducted in both the United States and Colombia that have confirmed HPV infection by PCR techniques report a prevalence of the oncogenic types of 6%-7%. 2,25 Recent studies suggest increasing trends in the incidence of HPV-associated HNC and an evident decrease in cases negative for the virus.…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies conducted in both the United States and Colombia that have confirmed HPV infection by PCR techniques report a prevalence of the oncogenic types of 6%-7%. 2,25 Recent studies suggest increasing trends in the incidence of HPV-associated HNC and an evident decrease in cases negative for the virus.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of detection was 6.6%. The types detected were HPV 11, HPV 43 and HPV 72 (Zambrano-Ríos et al, 2019).…”
mentioning
confidence: 99%